2004
DOI: 10.1111/j.1365-2125.2004.02183.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the cytochrome P450 CYP2C8 polymorphism on the disposition of (R)‐ibuprofen enantiomer in healthy subjects

Abstract: AimsTo study the effect of CYP2C8*3 , the most common CYP2C8 variant allele on the disposition of (R)-ibuprofen and the association of CYP2C8*3 with variant CYP2C9 alleles. MethodsThree hundred and fifty-five randomly selected Spanish Caucasians were screened for the common CYP2C8 and CYP2C9 mutations. The pharmacokinetics of (R)-ibuprofen were studied in 25 individuals grouped into different CYP2C8 genotypes. ResultsThe allele frequency of CYP2C8 * 3 (0.17) was found to be higher than that reported for other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
6
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 24 publications
(39 reference statements)
9
73
6
1
Order By: Relevance
“…The inferred CYP2C9 phenotype was related to a nearly-significant decrease of the formylated metabolite, as well as a significant decrease in the formylation ratio, among carriers of loss-of function CYP2C9 alleles. Most of this effect is attributable to the variant allele CYP2C9*3, whereas the presence of CYP2C9*2 was related to a weaker effect (see supplemental information Table S6), which is consistent with the weaker impairment in drug metabolism in vivo caused by CYP2C9*2 as compared to CYP2C9*3 [17,[30][31].…”
Section: Resultssupporting
confidence: 60%
“…The inferred CYP2C9 phenotype was related to a nearly-significant decrease of the formylated metabolite, as well as a significant decrease in the formylation ratio, among carriers of loss-of function CYP2C9 alleles. Most of this effect is attributable to the variant allele CYP2C9*3, whereas the presence of CYP2C9*2 was related to a weaker effect (see supplemental information Table S6), which is consistent with the weaker impairment in drug metabolism in vivo caused by CYP2C9*2 as compared to CYP2C9*3 [17,[30][31].…”
Section: Resultssupporting
confidence: 60%
“…CYP2C9 metabolizes R-and S-ibuprofen in vitro, with R-ibuprofen also being metabolized by CYP2C8. Consistent with this, three human studies showed that ibuprofen concentrations correlate with CYP2C9 genotype (Kirchheiner et al, 2002c;Garcia-Martin et al, 2004;Martinez et al, 2004b). The AUC of racemic ibuprofen was 1.6-and 1.8-fold higher in the *1/*3 and *3/*3 genotypes, due to elevated S-ibuprofen concentrations (1.5-and 1.7-fold, respectively).…”
Section: B Cyp2c9supporting
confidence: 58%
“…CYP2C8.3 has been shown to exhibit a lower paclitaxel 6a-hydroxylase activity in heterologous expression systems. However, in vivo the data are contradictory and opposite results have been obtained using different substrates (Dai et al, 2001;Niemi et al, 2003;Martinez et al, 2005). Other variant alleles with missense mutations are CYP2C8*2 and CYP2C8*4, but their impact on enzyme activity is unclear.…”
Section: Cyp2csmentioning
confidence: 89%